Understanding malaria treatment patronage from informal healthcare providers in Nigerian urban settlements: insights from community members and providers - Eniola A Bamgboye; Akintayo Olamide Ogunwale; Adamu Al-Mukhtar; Bello Musa; Laurette Mhlanga; Morenikeji Olawuwo; Adeniyi Fagbamigbe; Joshua Akinyemi; IkeOluwapo Ajayi; Ifeoma D Ozodiegwu (Malaria Journal)
Abstract Background Informal Healthcare Providers (IHCPs), including Proprietary Patent Medicine Vendors (PPMVs), drug peddlers, traditional healers, and herbal drug sellers are often the first choice for malaria treatment, especially in urban slums. Unplanned urbanization significantly impacts malaria transmission by creating cities with inadequate safety nets and healthcare access, increasing reliance on IHCPs. While the World Health Organization recognizes IHCP’s crucial role and emphasizes integrating them into formal healthcare for improved malaria care, they lack requisite training in malaria management and operate outside official regulations, raising concerns about the quality of care they provide. Understanding IHCPs' perceptions and practices is essential for their proper integration. This study explored the perceived malaria burden, IHCPs’ competence in malaria treatment, and reasons for visiting IHCPs in various urban settlements from both community member and provider perspectives. Methods This qualitative cross-sectional study was carried out in Ibadan and Kano metropolises. Eighteen Focus Group Discussions among 157 adult community members and twelve Key-Informant Interviews among PPMVs, drug peddlers, traditional healers and herbal drug sellers were conducted in these cities. Participants were drawn purposively from settlements—designated as formal, informal, and slum based on local definitions—in selected wards within the cities. Data were collected using pre-tested guides and analysed thematically. Results This study reveals that malaria remains a significant health problem in these Nigerian cities. Patronage of IHCPs generally is driven by affordable treatment, perceived mildness of illness, and access to credit facilities. However, cultural belief was key to patronage of traditional healers and herbal drug sellers, largely among informal and slum residents. Furthermore, while IHCPs had a strong perceived competence in managing malaria cases, inadequate diagnosis and treatment were standard practices. Conclusions IHCPs remain consistently patronized across urban settlements. Educating and equipping IHCPs with diagnostic tools, enhancing access to affordable healthcare, and raising public awareness is crucial for proper malaria management and promoting collaborations with formal healthcare providers.